An increase in hydrogen production from light and ethanol using a dual scale porosity photocatalyst. Issue 10 (25th April 2018) - Chen, Y. X.; Gombac, V.; Montini, T.; Lavacchi, A.; Filippi, J.; Miller, H. A.; Fornasiero, P.; Vizza, F.
Abstract : The stable photocatalytic production of hydrogen is demonstrated under simulated solar irradiation from the aqueous solutions of ethanol over a dual porosity 3D TiO2 nanotube array (TNTA). Abstract : The stable photocatalytic production of hydrogen is demonstrated under simulated solar irradiation from the aqueous solutions of ethanol over a dual porosity 3D TiO2 nanotube array (TNTA). The photocatalytic material consists of a uniform layer of TNTAs grown on each titanium fiber of a commercial sintered titanium web (TNTA-web). Under simulated solar irradiation, a stable H2 production rate of 40 mmol h −1 m −2 is observed. In comparison, TNTAs grown on a flat titanium foil (TNTA-foil) do not produce H2 under the same conditions. The addition of small (4–5 nm) and well distributed Pd nanoparticles to the TNTA-web increases the production of hydrogen to 130 mmol h −1 m −2 with a solar-to-fuel efficiency of 0.45%. The same Pd loading on the TNTA-foil support resulted in a H2 production rate of 10 mmol h −1 m −2 . Each catalytic material is characterized by a combination of SEM, HR-TEM, XRD, XPS and Raman spectroscopy. The enhancement in H2 production is attributed to the increased light absorption properties of the TNTA-web material enabled by its unique dual porosity. The analysis of the reaction by-products shows that ethanol is transformed into acetaldehyde as a single oxidation product. Additionally, it is shown that an optimal Pd loading maximizes the H2 production rate, since agglomeration of the metal nanoparticles takes place at high loading, decreasing the Pd–TiO2 interface where the photoreforming reactions take place.